2015
DOI: 10.1093/schbul/sbu195
|View full text |Cite
|
Sign up to set email alerts
|

Schizotypy as An Organizing Framework for Social and Affective Sciences

Abstract: Schizotypy, defined in terms of commonly occurring personality traits related to the schizophrenia spectrum, has been an important construct for understanding the neurodevelopment and stress-diathesis of schizophrenia. However, as schizotypy nears its sixth decade of application, it is important to acknowledge its impressively rich literature accumulating outside of schizophrenia research. In this article, we make the case that schizotypy has considerable potential as a conceptual framework for understanding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 74 publications
5
98
0
2
Order By: Relevance
“…Both impaired, 89 and enhanced 87,88,90 egocentric mental rotation performance have been reported in relation to elevated schizotypy. These findings have implications for social cognitive abilities (see Cohen et al 15 ), notably theory-of-mind because one crucial aspect of mentalizing involves visuospatial perspective taking and simulation. 91 Although enhanced egocentric perspective-taking ability may be associated with increased empathy, 88 in particular in women 91 and as a function of life experience, 93 excessive perspective-taking could lead to reduced agency and dissociative experiences.…”
Section: Imagery and Representationmentioning
confidence: 83%
See 1 more Smart Citation
“…Both impaired, 89 and enhanced 87,88,90 egocentric mental rotation performance have been reported in relation to elevated schizotypy. These findings have implications for social cognitive abilities (see Cohen et al 15 ), notably theory-of-mind because one crucial aspect of mentalizing involves visuospatial perspective taking and simulation. 91 Although enhanced egocentric perspective-taking ability may be associated with increased empathy, 88 in particular in women 91 and as a function of life experience, 93 excessive perspective-taking could lead to reduced agency and dissociative experiences.…”
Section: Imagery and Representationmentioning
confidence: 83%
“…Such work is critically needed to identify domains where schizotypy differs from schizophrenia, pointing to protective or compensatory mechanisms. 8 see also Herzig et al 10 Second, people with high levels of schizotypy display maladaptive behaviors, such as smoking 11 and drug use, 12 and they suffer lower social, educational, and professional levels of functioning, impoverished quality of life, and high levels of distress 13,14 (also see Cohen et al 15 as well as Mohr and Claridge 16 ). Therefore, schizotypy is an important research topic in its own right because a characterization of cognitive and neural processes in schizotypy may improve our mechanistic understanding of these disturbances and aid the development of intervention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Cohen et al (2015) suggested that schizotypy assessed in different cultures has the potential to provide us with information on cultural differences in social and affective functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Kwapil et al (2012) argued that comparable dimensional structures in cross-cultural samples would lend further support to the i) continuum model of schizotypy and schizophrenia spectrum disorders and ii) validity and utility of these measures in cross-cultural research. Cohen et al (2015) suggested that schizotypy assessed in different cultures has the potential to provide us with information on cultural differences in social and affective functioning. At the moment, few studies have been conducted to test the cross-cultural equivalence of the schizotypal personality traits (Fonseca-Pedrero, Compton, et al, 2014;Ortuño-Sierra et al, 2013) and schizotypy dimensions (Kwapil et al, 2012;Sierro et al, in press).…”
mentioning
confidence: 99%
“…eine Standardabweichung [26,70]. Mit dem Ausprägungsgrad basaler kognitiver Dysfunktionen geht auch eine analog beeinträchtigte Verarbeitung wichtiger sozial-affektiver Informationen einher, die grundlegend für eine funktionstüchti-ge "theory of the mind" sind [21].…”
Section: Neurobiologische Und Neuropsychologische Befunde Zur Schizoiunclassified